THE EFFECT OF INDIVIDUAL FACTORS ON CONSUMER’S PURCHASING DECISIONS AT GRAND DUCK KING RESTAURANT CAMBRIDGE MEDAN - Sri Aprianti Tarigan; Tina Linda; Susanto; Elyzabeth Wijaya; Erina Alimin (Bajang Institute, 2022)
The personality individual factors that usually affect consumers‘ purchasing decisions include age or life cycle stage, job, economic condition, lifestyle and personality or self-image. The consumer‘s purchasing decisions related to goods depends on various factors such as brand, quality, after sales services, warranty, advertising, rebates, offers, discount, mode of payment, display, sales person behaviour, store location and many more. Grand Duck King Restaurant Medan, it has been confirmed that the number of consumers has been decreasing these recent months. It has been suspected that this problem is due to consumers‘ individual factors. The indicators of individual factors in this research were adopted by Rouzbahani, et.al (2013:1151) which include age and life cycle stage, job, economic condition, lifestyle, and personality or self-image and indicators of consumer‘s purchasing decisions indicators by Lopez (2012:127) which are frequency of transactions, consumer referral, Loyalty, repeat decisions. The population that the writer used is the consumers the writer doing research 1 day on 30th May 2017 at grand Duck King Cambridge Medan which are 101 people, by using Slovin‘s Formula, the sample size is 81 consumers, and use the simple random sampling technique which the consumers have same chance to be chosen as sample. The results from analysis are individual factors have effect on consumer‘s purchasing decision at Grand Duck Restaurant King Cambridge Medan and individual factors have a strong and positive effect on consumer‘s purchasing decisions at Grand Duck King Restaurant Cambridge Medan.